Refugee Protection in Multi-level Governance Regimes: A Case for Kenya and Indonesia - Vincent G. Yatani (Faculty of Law Universitas Lampung, 2023)
In Indonesia, The Presidential Regulation No. 125 of 2016 concerning the management of asylum seekers, signed by President Joko Widodo on the last day of 2016, formalizes the role of sub-national units in refugee management, including the provision of appropriate, non-custodial accommodation. While in Kenya, the recently enacted Refugee Act of 2021 alludes to the engagement of the County Governments in Refugee protection. Within the context of the legal framework of these two countries, this article analyses the place of refugees in a multi-layered governance system through a comparative appraisal of local government structures in the selected States. The Article compares forms of decentralization adopted in these two refugee-hosting countries with the primary aim of establishing local government formation responsive to asylum seekers' plight. The research finds a novelty that involving local governments in refugee protection is a crucial step toward the effective and sustainable management of displaced populations. However, for it to be effective, it must be supported by adequate resources, clear guidelines, and a strong institutional capacity.